Non adherence to secondary prophylaxis for rheumatic fever - Saha, Santosh K.; Choudhury, Kamrun N.; Sarker, Nihar R.; Ahmed, Gias U.; Hoque, Nazmul (International Journal of Contemporary Pediatrics, 2020)
Background: Secondary prophylaxis with benzathine penicillin G (BPG) is a cost-effective intervention for preventing morbidity and mortality related to rheumatic fever (RF). There is no reliable data available with regards to adherence to secondary prophylaxis and rates of recurrent RF in many developing countries, including Bangladesh. So, aim of this study was to estimate rate of non-adherence and find out risk of non-adherence to secondary prophylaxis for rheumatic fever. Methods: Total 230, 5-30 years patients of both sexes with definite previous history of RF taking secondary prophylaxis with injection benzathine penicillin G (BPG) were enrolled by simple random fashion. Last one-year injection profile of the patient was collected from the injection card. Patients were then classified as “non-adherent” when the rate of adherence was <80% of the expected injections and as “adherent” when it was ≥80%. After collection of data selective patients were invited for blood tests and echocardiography to identify recurrence of rheumatic fever. Results: Out of 230 patients, male were 96 (41.7%) and female were 134 (58.3%). Male and female ratio was 0.7. 173 (75.2%) were adherent with benzathine penicillin and 57 (24.8%) patients not adherent with benzathine penicillin. In adherent group only 5 (2.2%) and in non-adherent group 19 (8.3%) patients develop rheumatic recurrence and this finding was statistically significant (p-value 0.001). Conclusions: Non adherence to secondary prophylaxis with BPG was found a major risk factor for recurrent rheumatic fever. The main reasons of non-adherence were lack of counselling, fare of pain and fail to remember.